Personalized Promotion on Consumer Spending Patterns in Online Food Delivery Services - Aquino, Rommel; Bolledo, Alexa; Condado, Joshua; Eleccion, Carl; Gutierrez, Jayson Kurt; Panganiban, Samanta (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of personalized promotions on consumer spending patterns in online food delivery services. Specifically, it investigated how discount offers and coupons, tailored recommendations, time-sensitive or event-based promotions, push notifications and rewards, and loyalty programs affect purchase frequency, order value, platform preference, engagement, and consumer loyalty. The study was anchored on the Input-Process-Output model, where references and respondents served as inputs, survey formulation and assessment procedures served as the process, and a proposed strategic promotional plan served as the output. A quantitative descriptive-correlational research design was used. The study involved ninety respondents from Sta. Mesa, Manila, selected through purposive sampling because they had experience using online food delivery services and personalized promotions. Data were gathered using a validated survey questionnaire and analyzed through percentage, weighted mean, Likert-scale interpretation, and Pearson correlation. The findings showed that the respondents were largely young adult users of online food delivery platforms, with GrabFood emerging as the most preferred application and most respondents spending within a moderate range per order. Personalized promotions were found to influence spending behavior, with tailored recommendations identified as the strongest promotional driver because they matched consumers’ preferences and encouraged product discovery. Discount offers and coupons affected the timing of purchases, while time-sensitive and event-based promotions moderately influenced urgency and purchasing decisions. Push notifications and rewards increased promotional awareness and app engagement, while loyalty programs encouraged platform preference and customer retention. The study also found a very strong positive relationship between personalized promotions and consumer spending patterns, with correlation values ranging from approximately 0.9986 to 0.9998, leading to the rejection of the null hypothesis. A major challenge identified was app fatigue, particularly when consumers received excessive or poorly timed promotional alerts. The study concludes that personalized promotions significantly influence consumer purchasing behavior and can strengthen customer engagement, sales performance, and platform loyalty when properly designed. It recommends improving AI-driven recommendation systems, using dynamic and personalized coupon structures, strengthening loyalty programs, improving notification relevance, and designing campaigns for broader consumer segments. The study aligns with SDG 8 on Decent Work and Economic Growth, SDG 9 on Industry, Innovation and Infrastructure, and SDG 12 on Responsible Consumption and Production. Its sustainability impact lies in supporting economic, technological, and consumer-welfare sustainability by promoting data-driven, responsible, and efficient digital marketing practices in online food delivery services.
Keywords: Consumer Spending Patterns; Discount Offers and Coupons; Loyalty Programs and Rewards; Online Food Delivery Services; Personalized Promotions; Push Notifications; Tailored Recommendations; Time-Sensitive Promotions